Dekontruksi Narasi Utsmani dalam Studi Al-Qur'an: Analisis Komparatif Tafsir At-Thabari dan Kritik John Wansbrough - Majid Abiyi, Royan; Mutma'inah, Mutma'inah (Islamic Religious Education Departement, 2026)
This study examines the deconstruction of the Uthmani Mushaf narrative in Qur’anic studies through a comparative analysis of At-Thabari’s classical interpretation of Q.S. Al-Baqarah (2):2 and John Wansbrough’s historical-critical approach. The aim of this research is to investigate how the concepts of revelation, textual authority, and the narrative of salvation are constructed within normative Islamic exegesis and how they are challenged by modern historical criticism. This research employs a qualitative, library-based method with clearly defined stages, including the collection of primary and secondary sources, content analysis of Jamiʿ Al-Bayan, a critical examination of Qur’anic Studies and The Sectarian Milieu, and an epistemological comparison of the two interpretive frameworks. The findings indicate that At-Thabari understands revelation as a certain and transcendent reality that underpins spiritual transformation and salvation for the God-conscious, whereas Wansbrough interprets the certainty of revelation as an ideological construct shaped by the dynamics of the early Muslim community. The significance of this study lies in demonstrating that the Uthmani Mushaf functions not merely as a product of codification or a symbol of political authority, but also as a mechanism for stabilizing meaning that enabled the emergence of a normative exegetical tradition in early Islam, while simultaneously opening a critical dialogue between theological faith and modern academic approaches in Qur’anic studies.